Transcatheter aortic valve replacement versus surgical aortic valve replacement in low‐surgical‐risk patients: An updated meta‐analysis. Issue 1 (21st October 2019) - Goel, Sunny; Pasam, Ravi T.; Wats, Karan; Patel, Jignesh; Chava, Srilekha; Gotesman, Joseph; Malik, Bilal A.; Frankel, Robert; Shani, Jacob; Gidwani, Umesh
Abstract: Objective: The purpose of this meta‐analysis is to compare the safety and efficacy of transcatheter aortic‐valve replacement (TAVR) to surgical aortic valve replacement (SAVR) in low‐surgical‐risk patients. Background: TAVR is proven to be safe and effective in patients with high‐ and intermediate‐risk aortic stenosis. However, there is limited data on the safety and efficacy of TAVR in patients with low surgical risk. Methods: We conducted an electronic database search of all published data for studies that compared TAVR to SAVR in low‐surgical‐risk patients (mean society for thoracic surgery [STS] score <4% and/or logistic EuroScore <10%) and reported on subsequent all‐cause mortality, cardiac mortality, stroke rates, and other outcomes of interest. Event rates were compared with a forest plot of odds ratio using a random‐effects model assuming interstudy heterogeneity. Results: A total of seven studies ( n = 6, 293 patients; TAVR = 2, 912; and SAVR = 3, 381) were included in the final analysis. There was no significant difference between TAVR and SAVR in terms of all‐cause mortality (OR 0.82; 95% CI 0.50–1.36, I 2 = 51%), cardiac mortality (OR 0.57; 95% CI 0.32–1.02, I 2 = 0%), new pacemaker implantation (OR = 3.11; 95% CI 0.58–16.60, I 2 = 89%), moderate/severe paravalvular leak (PVL; OR 3.50; 95% CI 0.64–19.10, I 2 = 54%) and rate of stroke (OR 0.63; 95% CI 0.34–1.15, I 2 = 39%) at 1‐year follow‐up. TAVR was found to have a significantly lower incidence of atrial fibrillation (AF; OR 0.15, 95% CI 0.10–0.24, I 2 = 38%) as compared to SAVR. Conclusion: The results of our meta‐analysis demonstrate similar rates of all‐cause mortality, cardiac mortality, and stroke at 1‐year follow‐up in patients undergoing TAVR and SAVR. TAVR is associated with a lower incidence of AF relative to SAVR. However, there was a significantly higher incidence of PVL with TAVR compared to SAVR.